2015
DOI: 10.2147/dddt.s82712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the efficacy and safety of a medical device in various forms containing Triticum vulgare for the treatment of venous leg ulcers – a randomized pilot study

Abstract: This study was carried out to assess the efficacy and tolerability of the topical application of an aqueous extract of Triticum vulgare (TV) in different vehicles (cream, impregnated gauzes, foam, hydrogel, and dressing gel) for the treatment of venous lower leg ulcers. Fifty patients were randomized to receive one of the five investigational vehicles. Treatment was performed up to complete healing or to a maximum of 29 days. The wound size reduction from baseline was the primary efficacy variable, which was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
1
14
0
3
Order By: Relevance
“…A specific aqueous extract of Triticum vulgare (TVE-DAMOR) manufactured by Farmaceutici DAMOR (Naples, Italy) is currently an active component in the manufacture of certain pharmaceutical products already marketed in Italy and abroad under the brand name Fitostimoline ® , in the formulation of cream and medicated gauze and is commonly used for the treatment of decubitus ulcers, burns, scarring delays, dystrophic diseases, and in conditions in which it is necessary to stimulate re-epithelialization or tissue regeneration processes. In fact, it has been reported that the active component of Fitostimoline ® products (TVE) determines a marked acceleration of tissue repairing processes, stimulates chemotaxis and the fibroblastic maturation, and significantly increases the fibroblastic index, which are crucial points in the repairing processes [ 1 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A specific aqueous extract of Triticum vulgare (TVE-DAMOR) manufactured by Farmaceutici DAMOR (Naples, Italy) is currently an active component in the manufacture of certain pharmaceutical products already marketed in Italy and abroad under the brand name Fitostimoline ® , in the formulation of cream and medicated gauze and is commonly used for the treatment of decubitus ulcers, burns, scarring delays, dystrophic diseases, and in conditions in which it is necessary to stimulate re-epithelialization or tissue regeneration processes. In fact, it has been reported that the active component of Fitostimoline ® products (TVE) determines a marked acceleration of tissue repairing processes, stimulates chemotaxis and the fibroblastic maturation, and significantly increases the fibroblastic index, which are crucial points in the repairing processes [ 1 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Como resultado final se observó reducción en el área de la superficie de la lesión, con mayor eficacia en las presentaciones de crema >50% (p <0.0095) e hidrogel >50% (p <0.0014), y en los signos y síntomas clínicos de la enfermedad con mayor eficacia en la presentación de gasas, por lo que se concluye que el dispositivo médico puede ser útil para el tratamiento de úlceras venosas crónicas, puesto que actúa como un apósito protector y tiene un mayor efecto de curación en heridas de la piel aguda tales como aquellas traumáticas y las quemaduras superficiales (24).…”
Section: Triticum Vulgareunclassified
“…In particular, scientific evidence has documented that wheat sprout oil has been used in traditional Iranian medicine for dermotonic and skin beauty, face freckles, and the moisturizing and repair of the minute pores of face skin [6]. TVE is commonly used for the treatment of decubitus ulcers, venous leg ulcers, sores, burns, scarring delays, dystrophic diseases, and, more broadly, in the presence of problems that are related to re-epithelialization or tissue regeneration [4,[7][8][9]. This extract is currently an active component in the brand name Fitostimoline ® (Farmaceutici Damor S.p.A., Naples, Italy).…”
Section: Introductionmentioning
confidence: 99%